Pemanfaatan Solar Sel sebagai Sumber Energi Penerangan Tempat Parkir di Dillem Wilis Trenggalek - Erma Surya Yuliana; Nandang Mufti; M. Tommy Hasan Abadi; Nurul Hidayat; Hasan Ismail (I-Com: Indonesian Community Journal, 2024)
Trenggalek Regency is located on the southern coast of East Java, which has a beautiful Dutch heritage agrotourism site, namely Dillem Willis. The Dillem Wilis Agrotourism location is in Dompyong Village, Bendungan District, Trenggalek Regency. When visiting this tourist attraction, a cafe is the main icon and reference location. Caffe Dillem Wilis sells various local Dillem Wilis products such as coffee, cow's milk, essential oils, and others. However, there is no parking area around the cafe to protect visitors' vehicles. Apart from that, lighting around tourist attractions is very minimal. The application of solar canopies in tourist location parking lots is the latest innovation in efforts to promote renewable energy and sustainability in the tourism sector. This parking lot product is an appropriate technology (TTG) applied in Dillem Wilis agrotourism. This article discusses the implementation of solar canopy technology, combining solar panels with a parking roof structure to provide parking and lighting at tourist spots.